Influence of plyometrics on jump capabilities in technical and aesthetical sports - Mlsnová, G.; Luptáková, J. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2017)
The aim of the study was to examine the effect of plyometric exercises on explosive strength of lower extremities in girls performing of technical and aesthetical sports. Experiment was carried out on three groups; artistic gymnasts (VG, n = 15; age = 12.4 ± 0.7 years), fitness girls (VF, n = 15; age = 13.8 ± 1.9 years) and dancers (VD, n = 15; age = 13.8 ± 2 years). To check, the control group of general population was involved in the study (VK, n = 15; age = 13.9 ± 1.5 years). Following tests on jump ergometer Fitro Jumper were carried out at the beginning and at the end of experimental period: countermovement jump without and with arms swing and 10- second series of repeated vertical jumps. Plyometric program consisted of two plyometric units a week during thirty weeks. The results show that higher improvement in all evaluated tests achieved the group of fitness. In the countermovement jump without arm swing was observed improvement height of the jump 3.4 ± 1.4 cm (p < 0.00001), in the countermovement jump with arm swing 5.7 ± 1.5 cm (p < 0.00001), in difference of height of the jump between countermovement jump with and without arms swing 2.3 ± 1 cm (p < 0.00001), in ten second series of repeated vertical jumps without arms swing in the height of jump 4.2 ± 1.6 cm (p < 0.00001) and in power in active take off phase 8.8 ± 2.2 W.kg-1 (p < 0.00001). Based on finding the study and in coherence with data from literature, we can conclude the effect of plyometric exercises was effective in combination with specific-strength training. Jumping ability is limiting factor of sport performance in technical and aesthetical sports and implementation of plyometric exercises to the training is highly recommend. The high level of jump capabilities can improve the quality and technique of performance complex acrobatic elements and dance leaps thereby increasing overall evaluation of performance in selected sports.